Tumor Stimulus-Responsive Biodegradable Diblock Copolymer Conjugates as Efficient Anti-Cancer Nanomedicines - Šubr, Vladimír; Pola, Robert; Gao, Shanghui; Islam, Rayhanul; Hirata, Takuma; Miyake, Daiki; Koshino, Kousuke; Zhou, Jian-Rong; Yokomizo, Kazumi; Fang, Jun; Etrych, Tomáš (Journal of personalized medicine, 2022)
Biodegradable nanomedicines are widely studied as candidates for the effective treatment of various cancerous diseases. Here, we present the design, synthesis and evaluation of biodegradable polymer-based nanomedicines tailored for tumor-associated stimuli-sensitive drug release and polymer system degradation. Diblock polymer systems were developed, which enabled the release of the carrier drug, pirarubicin, via a pH-sensitive spacer allowing for the restoration of the drug cytotoxicity solely in the tumor tissue. Moreover, the tailored design enables the matrix-metalloproteinases- or reduction-driven degradation of the polymer system into the polymer chains excretable from the body by glomerular filtration. Diblock nanomedicines take advantage of an enhanced EPR effect during the initial phase of nanomedicine pharmacokinetics and should be easily removed from the body after tumor microenvironment-associated biodegradation after fulfilling their role as a drug carrier. In parallel with the similar release profiles of diblock nanomedicine to linear polymer conjugates, these diblock polymer conjugates showed a comparable in vitro cytotoxicity, intracellular uptake, and intratumor penetration properties. More importantly, the diblock nanomedicines showed a remarkable in vivo anti-tumor efficacy, which was far more superior than conventional linear polymer conjugates. These findings suggested the advanced potential of diblock polymer conjugates for anticancer polymer therapeutics.
Keywords: drug delivery; anticancer; HPMA conjugate; pirarubicin; diblock conjugate